Flagellin from Listeria monocytogenes Is Glycosylated with β-O-Linked N-Acetylglucosamine - Schirm, M. (American Society for Microbiology, 2004)
Glycan staining of purified flagellin from Listeria monocytogenes serotypes 1/2a, 1/2b, 1/2c, and 4b suggested that the flagellin protein from this organism is glycosylated. Mass spectrometry analysis demonstrated that the flagellin protein of L. monocytogenes is posttranslationally modified with O-linked N-acetylglucosamine (GlcNAc) at up to six sites/monomer. The sites of glycosylation are all located in the central, surface-exposed region of the protein monomer. Immunoblotting with a monoclonal antibody specific for β-O-linked GlcNAc confirmed that the linkage was in the β configuration, this residue being a posttranslational modification commonly observed in eukaryote nuclear and cytoplasmic proteins.